A magyar gazdaságpolitika elmúlt 25 éve – gazdaságtörténeti áttekintés a konvergencia szempontjából = The last 25 years of Hungarian economic policy - an outline of economic history with a view to convergence - Tóth, Zsuzsanna (Közép-Európai Közlemények, 2017)
The primary aim of this paper is to describe the major Hungárián economic political measures implemented in terms of convergence. The time horizon fór the analysis is the period from the régimé change to 2013. As far as the economic and political events are concemed, this nearly 25 years can be divided intő four markedly distinguishable periods: between 1990 and 1994, fundamental structural changes were implemented; 1995 ushered in a period of restriction and stabilisation; the period between 2000 and 2008 was characterised by mistaken decisions, while the period between 2009 and 2013 was riddled with the consequences of the global economic crisis and the prolonged recession. With a view to the fact that Hungary pursued an active economic policy in the period following the régimé change, I describe the effects of such an activity on our country’s convergence process from several aspects. My paper is nőt meant to define or provide an in-depth analysis of the issues related to convergence and catching up; it merely intends to emphasise the fact that the quarter of a century has proved insufficient to remedy the economic and social problems inherited from the former régimé or resulting from the régimé change.